Identification of Genius Loci on the Main Street of Kotagede - Wiratama, Army; Nurdina, Haira Najma; Mumulati, Ralf; Agustiananda, Putu Ayu P; Sholihah, Arif Budi (Jurnal Koridor, 2024)
Kotagede is one of the districts in Yogyakarta with many historical sites. However, because of the dense morphology of the area that is characterised by small alleys, creating an atmosphere gap between the main street and the village tourism kampung. One of Kotagede's attractions, the silver crafts industries, is a sector that utilises much of the main street space in the form of retail shops. This study aims to explore the character of silver craft industry on Kotagede's main streets using the genius loci phenomenological method. Three parameters of image, space and character were used as the unit of analysis to identify the spirit of the area on Mondorakan and Kemasan streets. The results of the literature study and field observations show that both streets function as landmarks and representations of the silver industry sites. The results of the study are expected to be one of the references in the implementation of the revitalisation of tourist areas in Kotagede.